Sensorineural hearing loss after neonatal meningitis: a single-centre retrospective study - Paul Clarke; Catherine Tremlett; Saumya Thomas; John Fitzgerald; Ankur Sharma; James M Leaf; Christine Cane; Claire Stuart (BMJ Publishing Group, 2022)
Babies in intensive care are at higher risk for meningitis and sensorineural hearing loss (SNHL). We reviewed the rate of SNHL among definite cases of bacterial/fungal meningitis in our neonatal intensive care unit over a 16-year period (2006-2021). We identified 16 confirmed meningitis cases among 16 070 admissions: 8 of 10 surviving infants with available diagnostic audiology had normal/satisfactory hearing while 2 of 10 had SNHL. Both infants with permanent hearing loss had been born extremely preterm and received potentially ototoxic antimicrobials. Larger studies are needed to clarify whether SNHL occurs mainly due to meningitis itself or to its antimicrobial drug treatment.